2023
DOI: 10.3390/cancers15072073
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Screening Eligibility and Referral Practices in Texas Organizations Serving People with Substance Use Disorders

Abstract: For people at elevated risk for lung cancer, lung cancer screening (LCS) reduces lung cancer mortality. People with non-nicotine substance use disorders (SUDs) have elevated rates of smoking compared with the general population, highlighting them as a priority population for LCS consideration. Although research has shown LCS is underutilized, there is little literature to inform whether organizations that serve individuals with SUDs have existing clinical protocols surrounding LCS. In the current study, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The University of Houston Institutional Review Board (IRB) concluded that this project did not meet the definition of human subjects research under 45 CFR 46.102 (I) (i.e., a systematic investigation, including research development, testing, and evaluation, designed to develop or contribute to generalizable knowledge); therefore, no IRB review/approval was necessary. Detailed recruitment procedures are described elsewhere ( Siddiqi et al, 2022 , Taing et al, 2022 , Jafry et al, 2022 , Britton et al, 2023 , Britton et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…The University of Houston Institutional Review Board (IRB) concluded that this project did not meet the definition of human subjects research under 45 CFR 46.102 (I) (i.e., a systematic investigation, including research development, testing, and evaluation, designed to develop or contribute to generalizable knowledge); therefore, no IRB review/approval was necessary. Detailed recruitment procedures are described elsewhere ( Siddiqi et al, 2022 , Taing et al, 2022 , Jafry et al, 2022 , Britton et al, 2023 , Britton et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%